The Colombia-Israel Nexus: Toward Historical and Analytic Contexts. - Field, Les W. (Latin American Research Review, 2017)
Israel's historical relationships with Argentina, Nicaragua, and Guatemala during the Cold War in the 1980s provides one context for understanding the parameters of Israeli foreign policy in the region. These relationships allied Israel with right-wing military regimes suppressing a variety of subversive others in Argentina and Guatemala and also a right-wing counterinsurgency in Nicaragua. In the post-Cold War era, the Colombian case is distinctive because conflict is shaped by a number of different armed actors, including the state, right-wing paramilitaries, left-wing insurgents and the narcotics industries. Israel's role in the complex Colombian milieu involves relationships with both the state and the parastate, both the military and the paramilitaries. The Israeli and Colombian states are substantively and conceptually intertwined around a common obsession with national security and armed conflict with subversive others of many types. I ask whether a special relationship sutures Israel to Colombia linked to the expanding interventions of paramilitaries and parastate apparatuses. This article provides historical and analytic contexts to elaborate the Colombia-Israel relationship, toward a future in which "peace" may play an important role.